Marshall Characteristics and Durability of Hot Rolled Sheet–Wearing Course Using Rubber Asphalt - Putri, Elsa Eka; Putri, Nilda Tri; Alqadri, Farid; Andriani, Andriani; Yosritzal, Yosritzal (Akademisi dan Saintis Indonesia (ASASI), 2024)
Many road damages are caused by road construction that does not follow standards, so evaluating road conditions and choosing the appropriate asphalt for each state is essential. So, in this study, the asphalt mixture was modified using rubber asphalt with a percentage of rubber of 7% in the Hot Rolled Sheet-Wearing Course (HRS-WC). This study aimed to identify the effect of rubber asphalt on Marshall's characteristics and durability in HRS-WC. The method in this study is the Marshall Test and the calculation of the durability index on the test specimen with an immersion time of 0.5, 24, 72, and 168 hours at a temperature of 60°C. From the test results, the Optimum Asphalt Content (OAC) value of the rubber asphalt mixture was 7.13% with Marshall characteristic values of 4078.686 kg, flow 3.266 mm, MQ 1270.676 kg/mm, VMA 21.487%, VFB 71.983%, and VIM 6.062%. From the durability test results, the Residual Strength Index (RSI) value entered the specification only until the 24-hour immersion time with a value of 94.891%. The First Durability Index (FDI) and Second Durability Index (SDI) values are positive, where the mixture loses strength with increasing immersion time. It can be concluded that using rubber asphalt in HRS-WC is good enough for pavement because almost all Marshall characteristics were included in the specifications used. The stability value in the rubber asphalt mixture is higher than that of the pen—60/70 asphalt mixture. However, the level of durability of the rubber asphalt mixture is relatively low because it can only last up to 24 hours of immersion. Therefore, HRS-WC using rubber asphalt is unsuitable in areas with low groundwater levels or areas that often flood.